Bivalve mollusks of the Kuril-Kamchatka Trench, Northwest Pacific Ocean: Species composition, distribution and taxonomic remarks. (September 2019) - Kamenev, Gennady M.
Highlights: Thirty-three bivalve species were found in the hadal of the Kuril-Kamchatka Trench. Fourteen species were first records for the Kuril-Kamchatka Trench. Five species were found at the maximum depth of the trench (over 9500 m). Fourteen species (identified species and morphospecies) (42.4%) are endemic to the hadal of the Kuril-Kamchatka Trench. The depth range of 6000–6999 m is a transitional zone between the abyssal and hadal. Abstract: The Kuril-Kamchatka Trench with a maximum depth of 9600 m is one of the deepest trenches of the World Ocean and has the second (to the Izu-Bonin Trench) largest area of hadal habitat. Investigation of the materials collected by the KuramBio II German-Russian expedition (RV Sonne, 2016) (8 stations), and three Russian expeditions (RV Vityaz, 1949, 1953, 1966) (16 stations) from the hadal zone of the Kuril-Kamchatka Trench (6000–9583 m depth) revealed a rich fauna of bivalves including 33 species (identified species and morphospecies) belonging to 15 families, of which 18 species (54.0%) were determined to the species level and 14 species (42.4%) were first recorded for the Kuril-Kamchatka Trench. Of the 33 species found in the Kuril-Kamchatka Trench, 15 species (45.5%) were recorded outside the trench at depths of less than 6000 m. Vesicomya sergeevi Filatova, 1971 and Parayoldiella ultraabyssalis (Filatova, 1971) formed the most abundant populations in the trench (72.9% of all specimens of bivalves collected by the KuramBio II expedition) and were predominant in samples from the trench bottom. In the hadal zone of the Kuril-Kamchatka Trench, 3 depth ranges (6000–6999, 7000–8999, 9000–9583 m) were distinguished that differ in the species composition of bivalves. The bivalve fauna of the upper hadal zone of the Kuril-Kamchatka Trench (depths 6000–6999 m) is characterized by the highest species richness (23 species) and is represented mainly (65.2%) by bathyal-hadal and abyssal-hadal species. This depth range is considered as a zone of transition between the abyssal and hadal zones. The fauna of this transitional zone is most closely connected with the fauna of the abyssal plain adjacent to the trench. At depths of more than 7000 m, the proportion of hadal endemics significantly increases (more than 66%). At the maximum depth of the trench (over 9500 m), only 5 species were recorded. Of the 18 identified species, only 6 species (33.3%) were found exclusively in the hadal zone of the trench. Photographs, taxonomic remarks and distribution are provided for all identified species that were found in the hadal zone of the Kuril-Kamchatka Trench. Taxonomic decisions herein: Bathyspinula vityazi (Filatova, 1964) is a distinct species and not a synonym of Bathyspinula calcarella (Dall, 1908); Ledella spinuliformis F. R. Bernard, 1989 is synonymized with Ledellina formabile Filatova and Schileyko, 1984; following Krylova (1993) Myonera demistrata Allen and Morgan, 1981 is considered as a synonym of Bathyneaera hadalis (Knudsen, 1970).